2018
DOI: 10.1111/idj.12352
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different detection criteria on caries estimates and risk assessment

Abstract: The inclusion of non-cavitated lesions impacted estimates of prevalence and extent of dental caries, mainly when ICDAS was used. No impact was observed on the association between caries and socio-economic variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
(33 reference statements)
1
18
0
Order By: Relevance
“…It is noteworthy to point out that only 2 examiners were involved in the data collection, one calibrated by the other, and that we used a popula-tion-based sample. This population can be classified as a low-caries population (mean DMF-T at the cavity level of 1.39 at 12 years of age [Alves et al, 2018]) with frank access to fluoridated water and to fluoridated toothpaste. In this respect, the present paper differs from the previous studies assessing lesion activity.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy to point out that only 2 examiners were involved in the data collection, one calibrated by the other, and that we used a popula-tion-based sample. This population can be classified as a low-caries population (mean DMF-T at the cavity level of 1.39 at 12 years of age [Alves et al, 2018]) with frank access to fluoridated water and to fluoridated toothpaste. In this respect, the present paper differs from the previous studies assessing lesion activity.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates were computed using different criteria to define the D component: WHO criterion, 22 including only cavitated lesions; modified WHO criterion, including the active non-cavitated and all the cavitated lesions. 23 Both criteria were used to calculate the DMFT index, defined as the number of decayed, missing or filled teeth. The different components of the index (DT, MT, FT) were also described separately.…”
Section: Discussionmentioning
confidence: 99%
“…1,24 Studies have consistently shown better oral health conditions among children with more educated parents. 23,26 The association between plaque and gingivitis, in relation to a higher caries index, has been frequently reinforced in epidemiological studies. 27,28,29 Regarding the dental attendance pattern, it is known that those who visit the dentist motivated by pain tend to show poorer oral health than those who visit the dentist for a routine examination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high discrepancy of association results found over articles points to a high degree of inconsistency. Differences in the diagnosis criteria and the exposure could result in different findings, and this issue has been comprehensively discussed on other healthcare issues [ 53 , 54 ]. The variation of TMD diagnostic criteria may impact its prevalence [ 1 ], and in our systematic review, it has probably changed the rate of association between stress and TMD.…”
Section: Discussionmentioning
confidence: 99%